2019
DOI: 10.1177/0008417419833409
|View full text |Cite
|
Sign up to set email alerts
|

Do occupational justice concepts inform occupational therapists’ practice? A scoping review

Abstract: Background. Occupational justice and related concepts can inform practices directed at injustice and the lack of rights in daily life. Brazilian ideas about social occupational therapy seem to be similar to these concepts about inequality. Purpose. This study aimed to answer the questions, “Do occupational justice concepts inform occupational therapists’ professional actions?” and “How are occupational justice concepts connected to Brazilian ideas about social occupational therapy?” Method. A secondary analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
0
20
0
3
Order By: Relevance
“…Finally, tele-health or tele-schooling solutions were often not prepared to accommodate the needs of people with disabilities [29], including children with special education needs and their families, who may be especially affected by school closures [30,31]. Overall, people with disabilities regularly experience social participation disparities when they are denied, excluded, or deprived from an equal opportunity to pursue meaningful occupations, so-cial roles, and social integration, when compared to people without disabilities [32,33]. In turn, these social participation disparities directly contribute to broader health disparities, as participating in meaningful occupations is a key determinant of human health and wellbeing [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, tele-health or tele-schooling solutions were often not prepared to accommodate the needs of people with disabilities [29], including children with special education needs and their families, who may be especially affected by school closures [30,31]. Overall, people with disabilities regularly experience social participation disparities when they are denied, excluded, or deprived from an equal opportunity to pursue meaningful occupations, so-cial roles, and social integration, when compared to people without disabilities [32,33]. In turn, these social participation disparities directly contribute to broader health disparities, as participating in meaningful occupations is a key determinant of human health and wellbeing [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…This work has raised crucial concerns regarding the boundaries established through these conditions, such as how they can lead to oppressive practices and perpetuate coloniality (Galvaan, 2021;Gerlach et al, 2018;Guajardo et al, 2015;Ramugondo, 2018). The ongoing power of these conditions is illustrated by two recent reviews of literature addressing occupational injustice (Benjamin- Thomas & Laliberte Rudman, 2018;Malfitano, de Souza, Townsend, & Lopes, 2019). Despite occupational justice being a concept designed to draw attention to sociopolitical forces, both reviews found a dominant tendency within research and practice-oriented articles to stay within an individualistic lens.…”
Section: Radically Reconfiguring Conditions Of Possibility In Occupational Therapymentioning
confidence: 99%
“…However, since the 1970s, innovative socially-focused, ethical, politically-astute and rights-based approaches to occupational therapy have been developing in Brazil (Galheigo, 2018;Malfitano et al, 2014aMalfitano et al, , 2014bMalfitano et al, , 2019. Galheigo (2005Galheigo ( , 2011aGalheigo ( , 2011bGalheigo ( , 2014 and colleagues (Barros et al, 2005;Barros et al, 2011) have provided English speakers with translated glimpses at Brazilian social occupational therapy practices that derive "from a critical standpoint" (Galheigo, 2005, p. 91); and exemplars of socially-engaged, critical occupational therapy practices in Chile (Alburquerque & Chana, 2011) and South Africa (Watson & Swartz, 2004) have provided further inspiration and guidance for the profession in the Global North.…”
Section: Introductionmentioning
confidence: 99%